The Effect Of Human Resource Quality On Performance With Supervision As An Intervening Variable In Government Villages In Dolok Masihul District Serdang Bedagai Regency - Marplusmi Sitepu; Kiki Farida Ferine (International Journal of Management, Economic and Accounting, 2025)
This study aims to determine the influence of Human Resources Quality (X) on Performance (Y) with Supervision (Z) as an Intervening variable in Village Government in Dolok Masihul District, Serdang Bedagai Regency. The type of research used is quantitative research. Data was collected using a questionnaire method which was distributed to 62 respondents who were Village Officials in the Village Government in Dolok Masihul District. The data analysis technique in this study uses the Structural Equation Modelling (SEM) method using SmartPLS 3.0 Software. The results of the analysis showed that the quality of human resources had a positive and significant effect on supervision, the quality of human resources had a positive and significant effect on performance, supervision had a positive and insignificant effect on performance, and the quality of human resources had a positive and insignificant effect on performance with supervision as an intervening variable.